Fundus image analysis for the detection of diabetic eye diseases-a review - Noronha, Kevin; Nayak, K. Prabhakar (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/